A Combination of Action Research and Reflective Journal Writing in an English as a Foreign Language Class: Learners’ Psychological Point of Views and Their Grammar Use in Writing - Tahmasbi, Soheila; Karimnia, Shabnam; Rahimi, Ali (Frontiers in Psychology, 2022)
Action research and reflective thinking can enhance learning since both processes provide students with opportunities to step back and think about how they actually solve problems. While there is robust academic inquiry on reflection practices and action research in educational setting, investigating learners’ reflections through action research practices can shed more light on related research. This study implemented reflective journal writing through action research and aimed to investigate 1) participants' views about reflective journal writing, 2) effects of journal writing on reflective thinking development and 3) learners' grammar use in writing. Eighty language learners formed the two experimental and control groups of the study. Possible relation between reflective thinking level and participants' final exam was checked. Analyses of participants’ journals, a semi-structured interview, questionnaires' results and final exam scores were considered. Findings showed that the participants had positive views about journal writing, and they could enhance their level of reflective thinking as well as their grammar use in writing; nevertheless, no relation between reflective thinking level and final exam scores of the participants was found. The methodology and the results of the study could be conducive to welcoming alternative methods of teaching and assessment that encourage learners' reflective practices and active engagements in language classes.